Dynamics of mucosal permeability and inflammation in collagenous colitis before, during, and after loop ileostomy - Münch, A (Copyright 2005 by Gut, 2005)
Collagenous colitis has become a more frequent diagnosis but the aetiology of this disease is still unknown. We describe a female patient with intractable collagenous colitis who was treated with a temporary loop ileostomy. She was followed clinically, histopathologically, and functionally by measuring mucosal permeability before surgery, after ileostomy, and after bowel reconstruction. In our case report, active collagenous colitis was combined with increased transcellular and paracellular mucosal permeability. Diversion of the faecal stream decreased inflammation of the mucosa and normalised epithelial degeneration and mucosal permeability. After restoration of bowel continuity, mucosal permeability was altered prior to the appearance of a collagenous layer.